Development of GUI for Detetection of Eye Disorders in Infants - et. al., Aditya Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Strabismus is one of the most common vision diseases in which the eyes do not properly align with each other when looking at an object. The condition may be present occasionally or constantly and if it is present during a large part of childhood, it may result in amblyopia or loss of depth perception. In contrast to manual diagnosis, automatic recognition can significantly reduce labor cost and increase diagnosis efficiency. In this paper, we propose to detect ICD-10-CM Code H50.9 unspecified strabismus using CNN and Image Processing techniques. There are four types of strabismus namely exotropia, esotropia, hypertropia and hypotropia which we aim to detect. We furthermore aim to introduce a GUI particularly into pediatric ophthalmology where obtaining relevant diagnostic information is taxing.